PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KREATIF DAN KOLABORATIF MATA PELAJARAN IPAS PADA PESERTA DIDIK KELAS IV DI MADRASAH IBTIDAIYAH - Nurhayati, Emy; Sunardi; Prastiti, Tri Dyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the Project Based Learning (PjBL) model on the creative and collaborative thinking skills of fourth-grade students in the subject of Natural and Social Sciences (IPAS) at Madrasah Ibtidaiyah. The research employed a quasi-experimental method with a nonequivalent control group design. The subjects consisted of an experimental group taught using the PjBL model and a control group taught using conventional methods.The results show that there was a difference in the improvement of creative thinking skills between the experimental and control groups; however, the t-test indicated that this difference was not statistically significant (t = -1.192, df = 38, p = 0.241). This means that the application of the PjBL model did not significantly affect the enhancement of creative thinking skills. In contrast, for collaborative skills, the t-test revealed a statistically significant difference between the two groups (t = -5.766, df = 38, p < 0.001), with a mean difference of 10.82500, indicating that the PjBL model had a positive effect on students’ collaboration skills. Furthermore, the F-test showed that the calculated F value was greater than the F table value (17.156 > 3.592) with a p-value < α (0.000 < 0.050), leading to the rejection of H0. This indicates that, simultaneously, the PjBL model significantly influenced both creative and collaborative thinking skills.